Initial teacher training at a chilean university: graduates’ perception - Soto-Hernández, Valentina; Díaz, Claudio Heraldo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article presents the results of a research project addressing graduates’ perception about their initial teacher training at a university located in Chile’s Bío Bío region. An ad hoc instrument was based on the Good Teaching Framework and the Pedagogical Standards of the Ministry of Education. The results show high satisfaction with the training offered by the university; particularly as regards the training in disciplinary contents and the theoretical and practical training. The lowest level of satisfaction relates to the Chilean education system training, existing policies, and the teaching profession. An analysis by campuses revealed new findings: teachers who are linked to Los Ángeles Campus obtain significantly higher scores than those who are linked to the Concepción Campus. In the conclusion, plausible explanations for understanding this phenomenon are discussed and changes in teacher training curriculum are analyzed.